#TITLE_ALTERNATIVE# - AGUSTINUS (NIM : 13206142); Pembimbing : Dr. Ir. Pekik Argo Dahono, KRISBOA
Analysis of input current ripple in multiphase PWM inverters is proposed in this research. It begins with deriving the expression for the rms value of six-phase PWM inverters as a function of reference signal. Two configurations of six-phase double-winding (0 and 30 degree split) and two kinds of carrier signal modulation (single and double carrier) are used in the analysis. From the results, it is shown that the rms value of input current ripple in six-phase PWM inverter only influenced by the value of output current, modulation index, and load power factor. In the same input voltage and load conditions, the use of double carrier modulation signal in both configurations (0 dan 30 degree split) produce lower current ripple than using single carrier modulation signal. It is also found that the use of double carrier modulation signal in split 30o configuration produce lower rms value of input current ripple compared to split 0o configuration. Experiments are conducted and the results are provided to validate the analysis method which is proposed.